Improvement of assets management in commercial banks - Z.K. Nabiev (International Consortium of Education and Culture Research Studies, 2019)
This paper analyses the banking practice of the Republic of Uzbekistan as it is necessary to develop stock transactions related to the issue of commercial bills in foreign currency. This concludes increasing the quantity and quality of securities in the investment portfolio.